Konsorsium Pupuk Hayati Dan Amelioran Organik Terhadap Nitrogen Tanah Serta Pertumbuhan Padi (Oryza sativa L.) Pada Tanah Inceptisols - Adinda Putri Amanda; Betty Natalie Fitriatin; Emma Trinurani Sofyan (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2018)
Biofertilizer and organic ameliorant can be used alternative material to increase sustainable soil fertility  and yield for agricultur. This study aimed to investigate the effect of application biofertilizer consortium and organic ameliorant on chemical and biological character of soil and yield of rice in Inceptisols. The experiment was conducted in experimental field of Agriculture Faculty Universitas Padjadjaran from June until October 2017. Experimental design used a randomized block design of single faktor with twelve treatments and three replications. The treatments consist of control, solid biofertilizer, liquid biofertilizer, combination solid biofertilizer with organic amelioran (straw compost, charcoal husk and cow manure), liquid biofertilizer with organic amelioran, and organic amelioran independen. The result showed that biofertilizer consortium and organic ameliorant has significant effect on N soil and growth of rice. Solid biofertilizer and straw compost was the best treatment increase N soil.In general, biofertilizer consortium and organic ameliorant gave a significant influence for soil chemical and growth of rice. Key words: Biofertilizer, organic ameliorant, N soil and growth of rice.